2002
DOI: 10.1046/j.1432-1033.2002.02765.x
|View full text |Cite
|
Sign up to set email alerts
|

The DNA‐polymerase inhibiting activity of poly(β‐l‐malic acid) in nuclear extract during the cell cycle of Physarum polycephalum

Abstract: The naturally synchronous plasmodia of myxomycetes synthesize poly(b-L-malic acid), which carries out cell-specific functions. In Physarum polycephalum, poly (b-L-malate) [the salt form of poly(b-L-malic acid)] is highly concentrated in the nuclei, repressing DNA synthetic activity of DNA polymerases by the formation of reversible complexes. To test whether this inhibitory activity is cell-cycle-dependent, purified DNA polymerase a of P. polycephalum was added to the nuclear extract and the activity was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…To achieve a coordinated delivery of equilocally functioning proteins, molecular vehicles would have the advantage of stockpiling and carrying a number of different molecules jointly to defined loci, for example, nuclear proteins involved in DNA replication to nuclei. Previously, we have isolated a polyanion which could function in this regard ([5,6] and references therein). Poly(β‐ l ‐malate) is synthesized only in plasmodia and not in the other cell types of the life cycle.…”
mentioning
confidence: 99%
“…To achieve a coordinated delivery of equilocally functioning proteins, molecular vehicles would have the advantage of stockpiling and carrying a number of different molecules jointly to defined loci, for example, nuclear proteins involved in DNA replication to nuclei. Previously, we have isolated a polyanion which could function in this regard ([5,6] and references therein). Poly(β‐ l ‐malate) is synthesized only in plasmodia and not in the other cell types of the life cycle.…”
mentioning
confidence: 99%
“…We propose that the underlying mechanism by which PMLA increases the growth rate and shortens the duration of the cell cycle is the polymer‐inherent isosterism of the carboxylates with the array of phosphates in nucleic acids and, consequently, the competition with nucleic acids in the (reversible) binding of proteins, such as histones and DNA polymerases [5,6,10]. An example of competition between DNA polymerases and histones in the binding of PMLA has been demonstrated in a purified system [2] and was suggested as an explanation for the periodic activation of DNA polymerases in the cell cycle [11]. The degree of competition depends on the concentration of free PMLA, DNA, and the binding affinity and follows saturation functions.…”
Section: Resultsmentioning
confidence: 99%
“…A recent analysis of DNA synthetic activities in extracts of plasmodia revealed a cell cycle dependent inhibition and activation of DNA polymerases. This could be explained by the binding of DNA polymerases to endogenous PMLA in competition with periodically synthesized histones or certain other proteins [11]. Competition of this kind is likely to inhibit various kinds of activities involving the binding of proteins to nucleic acids, and it could affect cell growth and cell cycle duration.The distributing activity of PMLA and the efficiency of competition between PMLA and nucleic acids would both be influenced by the concentration of PMLA.…”
mentioning
confidence: 99%
“…Its presumed function is to coordinate transport, delivery, and activity of certain proteins (DNA polymerases, histones, etc.) to nuclei [3,7,10,19,20], and it has been suggested that it participates in the maintenance of the observed high degree of synchrony typical for plasmodia [8]. Strain M 3 CVII is one of the high PMLA producers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Of the various cell types in the life cycle of P. polycephalum , only the plasmodium contains the water soluble polymer, β‐poly( l ‐malate) (PMLA) [2–4]. The polymer is concentrated in the nuclei in an amount comparable with that of DNA and histones [5].…”
mentioning
confidence: 99%